2013
DOI: 10.5483/bmbrep.2013.46.9.234
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone induces the expression of LRRK2 and α-synuclein, two genes that when mutated cause Parkinson's disease in an autosomal dominant manner

Abstract: LRRK2 (leucine-rich repeat kinase 2) has been identified as a gene corresponding to PARK8, an autosomal-dominant gene for familial Parkinson’s disease (PD). LRRK2 pathogenicspecific mutants induce neurotoxicity and shorten neurites. To elucidate the mechanism underlying LRRK2 expression, we constructed the LRRK2-promoter-luciferase reporter and used it for promoter analysis. We found that the glucocorticoid receptor (GR) transactivated LRRK2 in a ligand-dependent manner. Using quantitative RT-PCR and Western a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The human neuroblastoma SH-SY5Y cell line is one of the most widely used dopaminergic cellular models with differentiation by retinoic acid. Moreover, treatment of cells with retinoic acid significantly increases LRRK2 expression [ 43 ] with little difference of p53 expression, increasing the possibility for LRRK2-mediated p53 phosphorylation (Additional file 2 : Figure S2). The differentiated cell lysates were co-immunoprecipitated with the p53 or LRRK2 antibody.…”
Section: Resultsmentioning
confidence: 99%
“…The human neuroblastoma SH-SY5Y cell line is one of the most widely used dopaminergic cellular models with differentiation by retinoic acid. Moreover, treatment of cells with retinoic acid significantly increases LRRK2 expression [ 43 ] with little difference of p53 expression, increasing the possibility for LRRK2-mediated p53 phosphorylation (Additional file 2 : Figure S2). The differentiated cell lysates were co-immunoprecipitated with the p53 or LRRK2 antibody.…”
Section: Resultsmentioning
confidence: 99%
“…This finding is in accordance with a recent study, which showed that dexamethasone increased the expression of two genes implicated in Parkinson's disease, the LRRK2 and α-synuclein. 36 Our study has some limitations. Our sample of 11 glucocorticoid-sensitive and 11 glucocorticoid-resistant subjects is small.…”
Section: Glucocorticoid-resistant (N = 11)mentioning
confidence: 89%
“…There is in vitro evidence implicating a role of disrupted GR signaling in PD molecular pathology. Administration of DEX to dopaminergic neurons disrupted GR signaling, resulting in an upregulation of α-synuclein protein levels ( 338 ). GC-mediated upregulation of α-synuclein levels has also been reported in peripheral blood mononuclear cells cultured from PD patients ( 339 ).…”
Section: Depression In Parkinson’s Diseasementioning
confidence: 99%